Sight - Vrettos, Adrienne Maria (New York : Margaret K. McElderry Books, 2007)
Sixteen-year-old Dylan uses her psychic abilities to help police solve crimes against children, but keeps her extracurricular activities secret from her friends at school
012 up
Keywords: Psychics -- Juvenile fiction; Missing children -- Juvenile fiction; High schools -- Juvenile fiction; Schools -- Juvenile fiction; Single-parent families -- Juvenile fiction; Criminal investigation -- Juvenile fiction; Psychics -- Fiction; Missing children -- Fiction; High schools -- Fiction; Schools -- Fiction; Single-parent families -- Fiction; Criminal investigation -- Fiction; Young adult fiction